Toxic and trace element analysis of surface sediments from the Gulf of Saros by INAA and XRF methods - Mukhamedshina, N.; Sarı, Erol; Mirsagatova, A. A.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (SPRINGER, VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS, 2007)
Some surface sediment samples, collected from 53 sampling sites of the Saros Gulf, were analyzed quantitatively by radioisotope energy dispersive X-ray fluorescence (EDXRF) and instrumental neutron activation analysis (INAA). Results indicated some correlations between Rb and Sr (r = 0.64), Fe2O3 and MnO (r = 0.59), Th and La (r = 0.71), Th and Ce (r = 0.64), Th and Sm (r = 0.60), concentration pairs. U and Th results are found to be compatible with those given in the literature for marine sediments.
Keywords: x-ray-fluorescence; black-sea; samples; contamination; Turkey; X-ışını flüoresans; Karadeniz; numuneler; bulaşma; Türkiye